Analysis of Neck Length and its Incidence for Cervical Spondylosis in Young Adults - Mohamed Taha, Fahim Haider Jafari, Prashant Kashyar, Mohammad RehanAsad, Waqas Sami, FawazFahad Al. Otaibi, (Journal of Rawalpindi Medical College, 2014)
Background:Background: Background: Background: Background: To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its incideincideincide incideincidence for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults Methods: Methods:Methods: Methods: In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck length in adultlength in adultlength in adultlength in adult length in adultlength in adultlength in adultlength in adultlength in adultlength in adultlength in adultlength in adultlength in adults ageage d 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls (n=192).(n=192).(n=192).(n=192).(n=192).(n=192).(n=192).(n=192). The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. The Length was The Length was The Length was The Length was The Length was The Length was The Length was The Length was The Length was The Length was The Length was determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external occipital protuberance t occipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance t occipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance t occipital protuberance toccipital protuberance to spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The distance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the perpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distance perpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distance perpendicular distanceperpendicular distanceperpendicular distance between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle of the mandible. of the mandible.of the mandible.of the mandible.of the mandible.of the mandible.of the mandible. of the mandible.of the mandible.of the mandible.of the mandible.of the mandible.of the mandible.of the mandible. The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital protuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wi protuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wi protuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wi protuberance to C7 spinous process wi protuberance to C7 spinous process wiprotuberance to C7 spinous process wi protuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wi protuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wi protuberance to C7 spinous process wi protuberance to C7 spinous process wiprotuberance to C7 spinous process wi th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level andandand Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer. Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer. Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer. Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer. Results: Neck pain, limited neck movement, headaches and inability to fully bend the neck were presenting complaint in 90.1 %. The severe cases(7.9%) showed additional symptoms like weakness in the arm and loss of grip, and weakness of the arms in association with the general symptoms making about 1.5 % of total cases. The average physical neck length in males was 110.31+12.71 and in females was 109.25+13.97.The average lordotic curvature in males was 1016.37+121.66 and the average curvature in females was 1020.22+118.05. Hyperlordosis (69.79%), hypolordosis(26.56%) and straight curves were (3.65%). The curvature of spine of patients was more than controls and the neck length of patients was less than that of controls. Conclusions: Curvature of cervical spine in patients with cervical spondylosis is more than that of controls. Also neck length in cervical spondylasis is less compared to controls.Background:Background: Background: Background: Background: To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its To analyze neck length and its incideincideincide incideincidence for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults nce for cervical spondolysis in young adults Methods: Methods:Methods: Methods: In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence In this comparative study, the incidence of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck of cervical spondylosis in patients with short neck length in adultlength in adultlength in adultlength in adult length in adultlength in adultlength in adultlength in adultlength in adultlength in adultlength in adultlength in adultlength in adults ageage d 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical 18 to 36 years with cervical spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls spondylosis (n=192), was compared with controls (n=192).(n=192).(n=192).(n=192).(n=192).(n=192).(n=192).(n=192). The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured The cervical spine curvature was measured on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. on the X rays using special software. The Length was The Length was The Length was The Length was The Length was The Length was The Length was The Length was The Length was The Length was The Length was determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external determined by drawing a line from the external occipital protuberance t occipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance t occipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance toccipital protuberance t occipital protuberance toccipital protuberance to spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 o spine of the C7 vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The vertebra.The distance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the istance was measured by taking the perpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distance perpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distanceperpendicular distance perpendicular distanceperpendicular distanceperpendicular distance between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external between the external occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle occipital protuberance to the C7 spine with angle of the mandible. of the mandible.of the mandible.of the mandible.of the mandible.of the mandible.of the mandible. of the mandible.of the mandible.of the mandible.of the mandible.of the mandible.of the mandible.of the mandible. The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and The physical cervical length and postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by postural variation was measured using inch scale by selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital selecting a point from external occipital protuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wi protuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wi protuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wi protuberance to C7 spinous process wi protuberance to C7 spinous process wiprotuberance to C7 spinous process wi protuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wi protuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wiprotuberance to C7 spinous process wi protuberance to C7 spinous process wi protuberance to C7 spinous process wiprotuberance to C7 spinous process wi th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of th the help of Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level Dewalt DW085K Self Leveling Plumb, Level andandand Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer. Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer. Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer. Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer.Square 5 Beam Laser Pointer. Results: Neck pain, limited neck movement, headaches and inability to fully bend the neck were presenting complaint in 90.1 %. The severe cases(7.9%) showed additional symptoms like weakness in the arm and loss of grip, and weakness of the arms in association with the general symptoms making about 1.5 % of total cases. The average physical neck length in males was 110.31+12.71 and in females was 109.25+13.97.The average lordotic curvature in males was 1016.37+121.66 and the average curvature in females was 1020.22+118.05. Hyperlordosis (69.79%), hypolordosis(26.56%) and straight curves were (3.65%). The curvature of spine of patients was more than controls and the neck length of patients was less than that of controls. Conclusions: Curvature of cervical spine in patients with cervical spondylosis is more than that of controls. Also neck length in cervical spondylasis is less compared to controls.